IMPLEMENTATION OF FLUTTER AND FIREBASE TECHNOLOGIES IN MODERN LIVE STREAMING APPLICATION DEVELOPMENT - Anmi, Fauzi Hidayatul; Jazman, Muhammad; Anofrizen, Anofrizen; Saputra, Eki; Siregar, Syafril; Ahsyar, T. Khairil (JOISIE (Journal Of Information Systems And Informatics Engineering), 2025)
Live streaming applications play a vital role in entertainment, education, and business communication. Despite their growing adoption, developing efficient and scalable live streaming applications remains challenging, particularly in ensuring real-time data synchronization, cross-platform compatibility, and optimal user experience under varying network conditions. This study addresses these challenges by designing and implementing a live streaming application using Flutter and Firebase, leveraging their advantages in cross-platform development and backend services. The research employs an Agile-Scrum methodology to iteratively develop and refine the application, incorporating essential features such as real-time video streaming, user authentication, live chat, and voice changers. Performance evaluation is conducted through direct user testing to assess functionality, responsiveness, and network adaptability. The results demonstrate that Flutter effectively streamlines the development of cross-platform interfaces, while Firebase ensures seamless real-time data synchronization and authentication. However, challenges persist in optimizing the application for low-spec devices and ensuring high-quality video streaming under limited bandwidth conditions. This study contributes to the field by providing a structured development approach for real-time live streaming applications, offering insights into best practices for integrating Flutter and Firebase. Future enhancements may explore automatic video quality adjustment and artificial intelligence-driven user interaction improvements to further refine the user experience.